The influence of communication satisfaction and organizational commitment on turnover intention / Saw Sze Syeh, Celine - Saw, Celine Sze Syeh (2012)
Employee turnover has gained considerable attention from all sectors and industries in Malaysia. Most organizations are aware of the fact that employee turnover intention is costly and when it happens, it is a huge lost to a company. It is definitely a great price to pay when organizations lose valuable talents especially those employees who are professional, highly productive and socially well connected to clients. As the issue of employee turnover becomes a hot topic, issues such as high commitments of employees and their attitude towards the organizations are being addressed. Studies showed that employees who are committed to their organizations tend to remain loyal and stay in the organizations. In order to gain benefits of employees’ commitment, good organizational communication and good level of employees’ satisfaction are essential. This is because communication satisfaction proved to have positive effects on employees’ commitment. The purpose of this study is to examine the level of communication satisfaction and determine the relationship between communication satisfaction and turnover intention mediated by organization commitment in organizations in Malaysia. The research instruments applied are the Communication Satisfaction Questionnaire (CSQ) and Down’s Commitment Scale (OCQ). Data are collected from 181 employees working in Malaysia. The results indicated that personal feedback has significant relationship with turnover intention mediated by affective commitment and normative commitment. Correlation test was used to examine the relationship direction between the variables and finally multiple regression analysis exposed that only personal feedback out of the five communication satisfaction variables was able to predict affective commitment and normative commitment. The relationship between affective and normative commitment and turnover intention was also identified in this research.